THYROGLOSSAL DUCT CYST: A DESCRIPTIVE STUDY OF 41 CASES - ., Asmat; ., Imad; ., Saeed (Journal of Postgraduate Medical Institute, 2011)
Objective: Material and methods Results: Conclusion: The most common presentation of thyroglossal duct cyst is a midline cystic swelling that moves with tongue protrusion. Thyroglossal duct cyst is present centrally in most of the cases. A total of 41 cases of thyroglossal duct cyst with a mean age of 16.7 + 17.49 years were included in the study. There were nineteen female and twenty two male patients. There were 9 recurrent and 32 cases. Forty patients presented with midline cystic swelling that moved with protrusion of tongue, seven with sore throat, 4 with dysphagia and 3 with globus. Forty (97.57) cases were central [9 (21.97%) suprahyoid and 31(75.60%) infrahyoid] and 01(2.43%) presented with cystic swelling on left side of the neck All the cases were subjected to sistrunk operation. : This descriptive study was conducted at the Department of ENT, District Headquarter Hospital Timergara from May 2001 to December 2007. The various presentations and management options were observed and documented using a semi structured proforma. Complications or recurrences, if any, were noted. To describe the clinical presentations and site distribution of the thyroglossal duct cyst.